ANALISIS PERSEPSI WORK CLIMATE, SUPPORTIVE MANAGEMENT, TERHADAP WORK EFFORT, DAN TAXPAYERâS SERVICE QUALITY YANG MEMPENGARUHI TAX EVASION DI KANTOR PELAYANAN PAJAK DALAM WILAYAH KANWIL JAWA BAGIAN BARAT II - -, Irwansyah (Jurnal Manajemen dan Keuangan, 2008)
This research explain and prove (1) influence of perception of employees of climate work and management support to effort work by parsial and together, (2) influence of perception of taxpayer of effort work to quality of service at tax payer and (3) influence quality of service tax at conducted by smuggling action is Taxpayer. This Subyek Research is 156 Office employees Service tax on Kanwil Java Part of West of II. Result of this research show the existence of positive influence of perception job climate, management support, effort work at quality of service, and negative influence to level smuggling tax.Keyword : work climate, management support, work effort, Taxpayerâs service Quality.